Pathomorphological Investigation on Vulvar Fibrosarcoma in A Buffalo - Chandratre, G. A.; Sushma; Lather, D.; Narang, G. (The Indian Journal of Animal Reproduction, 2021)
Fibrosarcoma a malignant mesenchymal tumour, is rarely reported in external genitalia of buffalo. A biopsy tissue sample of 6 years old female buffalo with a history of large round shape growth approx 250gms attached to dorsum of vulvar lips was received at Department of Veterinary Pathology, LUVAS, Hisar. Biopsy sample was processed for cytological and histopathological examinations which indicated fibrosarcoma. Masson’s Trichrome special stain (for fibers demonstration) and AgNOR (to confirm number of nucleoli in the nucleus) staining confirmed fibrosarcoma.